Isolation and anti-proliferative activity of natural products from green seaweed - Zulhedi Ilyas, Fitriyanti; Darnis, Deny Susanti; Mohammad Noor, Normawaty; Bakhtiar, M. Taher (2014)
Seaweeds are marine organism that is chemically rich in source of different bioactive compounds of secondary metabolites. Selected green seaweed has been commonly consumed as human food due to their nutrient content. However, huge numbers of bioactive metabolites from green seaweed has been unexplored yet. The aims of this study are to isolate phytochemical from selected Malaysian seaweed and to investigate the antiproliferative activity of isolated compounds. Seaweed is extracted by soxhlet extractor with using organic solvents for 24 hours, and then the crude seaweed is fractionated by vacuum liquid chromatography and column chromatography. The isolated compounds of seaweed are characterized by HRMS, FTIR spectroscopy, 1D and 2D NMR spectroscopy. They also are studied for their ability to inhibit cell proliferation of breast cancer cell MCF-7 using MTT assay. Two isolated compounds that were identified as Coumarin derivative showed activity against MCF-7.